Feasibility study on indigenous confectionery business – the case of gulo puan industries - Yuliati, Kiki; Hamzah, Ruth Samantha; Hamzah, Basuni (Economia agro-alimentare/Food Economy - Open Access, 2022)
Artisanal food industry from agricultural and livestock crops have major potential on improving local community welfare and even contributing to sustainability if they are processed, produced and marketed properly. Agricultural and dairy products can be processed into a more diverse range of products that can attract wider consumers, particularly burgeoning urban middle-class. However, studies on such industry, particularly those in low and lower-middle income countries, are disproportionally sparse in the literature. In this study, we examine economic viability of product diversification of swamp buffalo milk-based artisanal confectionery product named gulo puan, which is exclusively produced in Pampangan sub-district, Ogan Komering Ilir regency, South Sumatra, Indonesia. To improve its marketability, the diversification of gulo puan into chocolate bar-like products was proposed. Financial feasibility analyses with the investment criteria, namely NPV, Net B/C, IRR, payback period, and sensitivity analysis were conducted and show that the proposed implementation is viable, robust, and realistic. However, declining number of swamp buffaloes in recent years due to farming mechanization, as well as lack of infrastructure for supply chain, remain as challenges in the future that need to be addressed by stakeholders and policymakers.